Pembelajaran Pendidikan Agama Islam Berbasis Merdeka Belajar di SMPN 2 Semaka Kabupaten Tanggamus - Riadi, Setyo; Syefi’i, Imam; Rodhotul Jannah, Siti (CV. Bimbingan Belajar Assyfa, 2024)
Islamic Religious Education learning based on independent learning is the actualization of the formation of students'' character competencies. selection and use of learning media, selection and use of learning methods, skills in assessing student learning outcomes, and selecting and using learning strategies or approaches. The aim of this research is: 1) To analyze the learning planning for Islamic Religious Education based on independent learning 2) To analyze the implementation of Islamic Religious Education learning based on independent learning 3) To evaluate Islamic religious education learning. This research seeks to describe and analyze Islamic Religious Education Learning based on independent learning at SMPN 2 in Tanggamus Regency with a problem focus including planning, implementation and evaluation. This research uses a qualitative approach. This research uses case study research, and the location data obtained is not numbers but in the form of written and spoken words. Learning planning for Islamic Religious Education based on Freedom of Learning Based on observations, the results show that SMP Negeri 2 Semaka plans Islamic Religious Education learning by considering the vision, mission, goals and learning targets, as well as conducting research in each class. Implementation of Islamic Religious Education learning based on Freedom of Learning Observation results from Islamic Religious Education learning in class VII show that teachers use learning media without referring to teaching modules because learning in class is dynamic and changes according to class needs and approval. Evaluation of Islamic Religious Education learning based on independent learning Learning evaluation activities in class VII of SMP Negeri 2 Semaka show that students are motivated to better understand and use the material rather than just pursuing target grades. Implementation of Islamic Religious Education learning based on independent learning at SMP Negeri 2 Semaka holds Islamic Religious Education learning without teacher and student intervention in introductory, core and closing activities so that the learning atmosphere both inside and outside the classroom is carried out effectively. Evaluation of Islamic Religious Education learning outcomes at SMP Negeri 2 Semaka is carried out during the learning process (Formative) and at the end of the learning objectives (Summative).